ANALISIS PRAKTEK JUAL BELI DROPSHIPPING DALAM PERSPEKTIF EKONOMI ISLAM LATAR BELAKANG MASALAH - Risvan Hadi (AT-TAWASSUTH: Jurnal Ekonomi Islam, 2019)
In this Dropshipping system there are three related actors they are buyers, sellers (goods owners) and Dropshipper. The series of product sales through the Dropshipping system is when a customer has paid for a product to Dropshipper. Then Dropshipper pays the seller while sending details of the products ordered by the customers. Then the owner of the item will send the product directly ordered by the customer. This research aims to explain the scheme of buying and selling online with the Dropshipping system and analyzing online buying and selling with the Dropshipping system in the perspective of Islamic Economics. This research is a qualitative research. The results of this research conclude that Dropshipping is allowed in the perspective of Islamic Economics by using syirkah contracts, that is syirkah wujuh and simsarah (broker /agent). Both forms of this transaction can legalize Dropshipping buying and selling practices as long as there is no element of gharar / fraud. This Dropshipping practice is in accordance with Maqashid Syariah which will give a pattern of rational and substantial thinking in looking at forms of transactions to respond the growing business that continues to grow.